Use of Activity Trackers in Orthopaedics. Issue 19 (1st October 2019) - Garg, Sumeet; Quick, Hannah D.; Kim, Eun Bi; Erickson, Mark A.
Abstract : Activity trackers are relatively inexpensive, easily available, and widely used by consumers. There has been increased interest in healthcare practice and research to use activity tracker data. Continuous collection of health variables including step count, heart rate, and calorimetry provides researchers and clinicians data to monitor patients after an intervention and/or encourage physical activity. The purpose of this article is to review the current use of activity trackers in orthopaedics and discuss potential applications in clinical research.